Guidance on using the revised Logical Framework - How to note - DFID (DFID, 2011)
The principal changes to the logframe from the earlier (2008) 4 x 4 ma trix are: - Objectively Verifiable Indicators (OVIs) have been separat ed into their component elements (Indicator, Baseline and Target), and Milestones added. - Means of Verification has been renamed ‘Source’. - Inputs are now quantified in terms of funds (expressed in Sterling f or DFID and all partners) and use of DFID staff time (expressed as ann ual Full-Time Equivalents (FTEs). - A DFID Share box now indicates the financial value of DFID’s Inputs as a percentage of the whole. - Assu mptions are shown at Purpose and Output level only. - Risks are shown at Activities level only, but also rated at Output level; - At the Out put level, the Impact Weighting is now shown in the logframe together with a Risk Rating for individual Outputs. - Activities are now shown separately (so do not normally appear in the logframe sent for approva l), although they can be added to the logframe if this is more suitabl e for your purposes. - A renewed emphasis on the use of disaggregated beneficiary data within indicators, baselines and targets. The Logical Framework (logframe) was significantly re-designed in February 2009. In January 2011 a slightly amended logframe template was introduced at the same time as the launch of the new DFID Business Case. Given the extent of changes that took place in February 2009 it was only necessa ry to make minor amendments in January 2011. These amendments are as f ollows: - Results Chain terminology aligned across DFID (the terms Goa l and Purpose in the old logframe template have been replaced by Impac t and Outcome) - Rows added to allow achieved results to be captured a longside the planned results determined at project design stage - Word version of the logframe template removed – excel is the preferred for mat for logical frameworks from January 2011 - Indicator numbering int roduced within logframe template